2018
DOI: 10.1016/j.jpainsymman.2017.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Does Modality Matter? Palliative Care Unit Associated With More Cost-Avoidance Than Consultations

Abstract: Context Inpatient palliative care is associated with reduced costs, but the optimal model for providing inpatient palliative care is unknown. Objectives To estimate the effect of palliative care consultations (PCC) and care in a palliative care unit (PCU) on cost of care, in comparison with usual care (UC) only and in comparison with each other. Methods Retrospective cohort study, using multinomial propensity scoring to control for observed confounding between treatment groups. Participants were adults adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 41 publications
(58 reference statements)
2
26
1
1
Order By: Relevance
“…This organizational norm demonstrated lack of early PC, despite numerous studies that have shown that PC delivered simultaneously with standard oncology care from the time of diagnosis leads to a better quality of life, reduced costs, and less futile treatment. [21222324] Lack of guidelines for effective collaborative practice was found to be a key contributor to this organizational norm; this requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This organizational norm demonstrated lack of early PC, despite numerous studies that have shown that PC delivered simultaneously with standard oncology care from the time of diagnosis leads to a better quality of life, reduced costs, and less futile treatment. [21222324] Lack of guidelines for effective collaborative practice was found to be a key contributor to this organizational norm; this requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…These policies influence medical expenditures by affecting the relative or absolute prices of medical services and product [24]. The second level mainly referred to hospital characteristic factors, such as the diagnosis and treatment level [25][26][27], hospital management [28][29][30][31][32][33] and use of advanced medical devices [34][35][36][37][38][39]. The third level mainly referred to the patients characteristics, such as age [40], gender [41], education status [42], and health status [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that PCT consultation was associated with significant costs savings (on average €4,151 per hospital admission) for patients with cancer. Savings were higher for patients with more co‐morbidities (May, Normand, et al, ) and were mainly due to a reduced length of stay, less ICU admissions, and less medication and laboratory costs (May et al, ; May, Garrido, et al, ; Morrison et al, ; Penrod et al, ).…”
Section: Discussionmentioning
confidence: 99%